2023
DOI: 10.21203/rs.3.rs-2912362/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developing survey weights to ensure representativeness in a national, matched cohort study: results from the Children and young people with Long Covid (CLoCk) study.

Abstract: Background: Findings from studies assessing Long Covid in children and young people (CYP) need to be viewed in light of their methodological limitations. For example, if non-response and/or attrition over time systematically differ by sub-groups of CYP, findings could be biased and generalisation limited. The present study aimed to (i) construct survey weights for the Children and young people with Long Covid (CLoCk) study, and (ii) apply them to published CLoCk findings showing the prevalence of shortness of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…We have recently developed flexible survey weights to address potential bias and selection issues in the CLoCk study and have demonstrated that previously reported prospective findings from CLoCk (based on a sample similar to those presented in the current manuscript) are generalizable to the wider population of CYP in England. 55 , 56 Third, all relevant measures (eg loneliness, health outcomes etc.) were self-reported which is subject to biases and measurement errors.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently developed flexible survey weights to address potential bias and selection issues in the CLoCk study and have demonstrated that previously reported prospective findings from CLoCk (based on a sample similar to those presented in the current manuscript) are generalizable to the wider population of CYP in England. 55 , 56 Third, all relevant measures (eg loneliness, health outcomes etc.) were self-reported which is subject to biases and measurement errors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we do not have any information on additional infections since April 2022 when all community testing for SARS-CoV-2 was stopped. Additionally, although respondents in the main CLoCk study are broadly representative of the target population 23 , only 7.3% of those approached for this smaller Omicron sub-study participated at all time points. However, respondents to the Omicron sub-study are broadly similar to the target population, albeit with some differences (e.g., by region).…”
Section: Discussionmentioning
confidence: 99%
“…Equally, they could be less invested in being involved in a study than young people still experiencing symptoms. Overall, the participants in the main CLoCk study are largely representative of the target population 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Topic guides were informed by the CLoCk PPIE group to ensure questions were relevant to young people living with Long COVID. Participants were also recruited from the wider CLoCk study ( Stephenson et al, 2021 ), which initial analysis indicates is broadly representative of the population of young people in England ( Rojas et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%